2-Cell-like Cells: An Avenue for Improving SCNT Efficiency - Bo Fu; Hong Ma; Di Liu (Biomolecules, 2022)
After fertilization, the zygote genome undergoes dramatic structural reorganization to ensure the establishment of totipotency, and then the totipotent potential of the zygote or 2-cell-stage embryo progressively declines. However, cellular potency is not always a one-way street. Specifically, a small number of embryonic stem cells (ESCs) occasionally overcome epigenetic barriers and transiently convert to a totipotent status. Despite the significant potential of the somatic cell nuclear transfer (SCNT) technique, the establishment of totipotency is often deficient in cloned embryos. Because of this phenomenon, the question arises as to whether strategies attempting to induce 2-cell-like cells (2CLCs) can provide practical applications, such as reprogramming of somatic cell nuclei. Inspired by strategies that convert ESCs into 2CLCs, we hypothesized that there will be a similar pathway by which cloned embryos can establish totipotent status after SCNT. In this review, we provide a snapshot of the practical strategies utilized to induce 2CLCs during investigations of the development of cloned embryos. The 2CLCs have similar transcriptome and chromatin features to that of 2-cell-stage embryos, and we propose that 2CLCs, already a valuable in vitro model for dissecting totipotency, will provide new opportunities to improve SCNT efficiency.